Investigation of mold and blue stain fungi on rattan was conducted at the rattan industry, Cileungsi, Bogor on February 2005. The isolation and identification of fungi on rattan samples was done at the laboratory of Forest Pathology, Faculty of Forestry, Bogor Agricultural University, Indonesia. Rattan samples are cutted in size each 2 cm. Samples were growth and incubated on medium PDA (Potato Dextrose Agar) for 7 days in 29°C. There are two treatment, surface sterilized is used alcohol 70 % a - Elis Nina HERLIYANA (Departemen Hasil Hutan, IPB, 2009)
Investigation of mold and blue stain fungi on rattan was conducted at the rattan industry, Cileungsi, Bogor on February 2005. The isolation and identification of fungi on rattan samples was done at the laboratory of Forest Pathology, Faculty of Forestry, Bogor Agricultural University, Indonesia. Rattan samples are cutted in size each 2 cm. Samples were growth and incubated on medium PDA (Potato Dextrose Agar) for 7 days in 29°C. There are two treatment, surface sterilized is used alcohol 70 % and non surface sterilized. Each treatment was replicated 4 times. The identification of fungi was done manually using identification book Barnett (1986). The results showed that fungi dominantly formed from sterilized samples of rattan were Monilia sp. (55%) and Rhizophus sp. (32.5%). Whereas from non sterilized samples were Rhizophus sp. (54.77%) and than Monilia sp. (30.95%). Keywords : Rattan, Monilia sp., Rhizophus sp., mold fungi, blue stain fungi.